Reestruturação organizacional da coordenação de almoxarifado do departamento de materiais da Universidade Federal do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
Discusses the logistics processes managed by the Coordination for the Department of Materials Warehouse of the Federal University of Amazonas (UFAM-demat). Assumed that the modernization of procedures and tools for the logistic processes of supply of internal coordination of the demat Warehouse / UFAM can contribute to a better performance of that body providing feedback to the institution by reducing bottlenecks, rework and costs. Enrolls a literature review composed of materials management and modeling of business processes. It encourages a methodological path that characterizes the research as an exploratory case study. Uses a top down approach divided into three phases, starting with the preparation of the environment and the survey and description of the current situation (As Is). He points out that the results obtained enabled the identification and improvement of processes and allowed understanding of the desired situation to qualify the performance of the Federal University of Amazonas, thus enabling propose adjustments that would bring significant gains to the institution.
Keywords: Gestão de materiais; Modelagem de processos de negócio; UFAM; DEMAT; Materials management; Business process modeling; OUTROS